Parental age influences offspring telomere loss. (14th January 2016) - Heidinger, Britt J.; Herborn, Katherine A.; Granroth‐Wilding, Hanna M.V.; Boner, Winnie; Burthe, Sarah; Newell, Mark; Wanless, Sarah; Daunt, Francis; Monaghan, Pat
Summary: The age of the parents at the time of offspring production can influence offspring longevity, but the underlying mechanisms remain poorly understood. The effect of parental age on offspring telomere dynamics (length and loss rate) is one mechanism that could be important in this context. Parental age might influence the telomere length that offspring inherit or age‐related differences in the quality of parental care could influence the rate of offspring telomere loss. However, these routes have generally not been disentangled. Here, we investigated whether parental age was related to offspring telomere dynamics using parents ranging in age from 2 to 22 years old in a free‐living population of a long‐lived seabird, the European shag ( Phalacrocorax aristotelis ). By measuring the telomere length of offspring at hatching and towards the end of the post‐natal growth period, we could assess whether any potential parental age effect was confined to the post‐natal rearing period. There was no effect of maternal or paternal age on the initial telomere length of their chicks. However, chicks produced by older mothers and fathers experienced significantly greater telomere loss during the post‐natal nestling growth period. We had relatively few nests in which the ages of both parents were known, and individuals in this population mate assortatively with respect to age. Thus, we could not conclusively determine whether the parental age effect was due to maternal age, paternal age, or both; however, it appears that the effect is stronger in mothers. These results demonstrate that in this species, there was no evidence that parental age was related to offspring hatching telomere length. However, telomere loss during nestling growth was reduced in the offspring of older parents. This could be due to an age‐related deterioration in the quality of the environment that parents provide, or because parents that invest less in offspring rearing live to an older age. Abstract : Lay Summary